2009
DOI: 10.1007/bf03393072
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Intraverbal Behavior to Children with Autism: A Comparison of Textual and Echoic Prompts

Abstract: Although echoic prompts may be effective for teaching intraverbal behavior to children with autism, the performance of some children may become dependent on such prompts (i.e., the prompts cannot be eliminated). Recent research suggests that visual rather than echoic prompts may be used to teach children with autism a variety of skills and may facilitate independent performance. In the present study, an adapted alternating treatments design was used to compare the effects of using visual (textual) and echoic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 12 publications
(14 reference statements)
6
46
1
4
Order By: Relevance
“…Researchers have demonstrated the effectiveness of tact and textual prompting procedures in establishing intraverbals (Braam and Poling 1983;Luciano 1986). Furthermore, previous studies have directly compared echoic prompts to visual prompts for their effectiveness in establishing intraverbal responding and have generally found that the use of visual prompts resulted in more rapid acquisition (Ingvarsson and Hollobaugh 2011;Vedora et al 2009) or higher levels of correct responding (Finkel and Williams 2001).…”
mentioning
confidence: 99%
“…Researchers have demonstrated the effectiveness of tact and textual prompting procedures in establishing intraverbals (Braam and Poling 1983;Luciano 1986). Furthermore, previous studies have directly compared echoic prompts to visual prompts for their effectiveness in establishing intraverbal responding and have generally found that the use of visual prompts resulted in more rapid acquisition (Ingvarsson and Hollobaugh 2011;Vedora et al 2009) or higher levels of correct responding (Finkel and Williams 2001).…”
mentioning
confidence: 99%
“…The intraverbal is considered one of the most essential, yet difficult verbal operants for children with autism to acquire (Sundberg and Michael 2001). For this reason, several different procedures have been examined to teach intraverbal behavior to this population including transfer of stimulus control (Ingvarsson and Hollobaugh 2011;Partington and Bailey 1993;Vendora, Meunier, and Mackay 2009), match-to-sample or listener training (Miguel, Petursdottir, and Carr 2005;Petursdottir, Carr, Lechago, and Almason 2008a;Petursdottir, Olafsdottir, and Aradottir 2008b), multiple exemplar instruction (MEI; Fiorile and Greer 2007;Greer, Yuan, and Gautreaux 2005;Nuzzolo-Gomez and Greer 2004), and tact training (Coon and Miguel 2012;Dounavi 2011;May, Hawkins, and Dymond 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Results of comparison studies indicate that echoic-to-intraverbal is more efficient than tact-tointraverbal transfer for some learners (Ingvarsson and Le 2011), tact-to-intraverbal is more efficient than echoic-to-intraverbal transfer for other learners (Ingvarsson and Hollobaugh 2011), and that textual-to-intraverbal is more efficient than echoic-tointraverbal for some learners (Finkel and Williams 2001;Vedora et al 2009). The efficiency of each procedure is likely a product of participant learning history (Coon and Miguel 2012).…”
mentioning
confidence: 97%
“…Tact-to-intraverbal (Goldsmith et al 2007), echoic-to-intraverbal (Bloh 2008;Ingvarsson and Le 2011), receptive-to-intraverbal (Bloh 2008), and textual-tointraverbal (Finkel and Williams 2001;Vedora et al 2009) procedures for transferring stimulus control have proven effective for establishing intraverbals. Results of comparison studies indicate that echoic-to-intraverbal is more efficient than tact-tointraverbal transfer for some learners (Ingvarsson and Le 2011), tact-to-intraverbal is more efficient than echoic-to-intraverbal transfer for other learners (Ingvarsson and Hollobaugh 2011), and that textual-to-intraverbal is more efficient than echoic-tointraverbal for some learners (Finkel and Williams 2001;Vedora et al 2009).…”
mentioning
confidence: 99%